The Endangered Coastal Fishers along the Coast of the Archipelago Sea. The Environmental Conflict in Policy-making - Sonck-Rautio K (Finland, 2022)
The small-scale fisheries of the Finnish archipelago are in crisis. Three major
problems were identified during an ethnographic study of the different stake-
holders in the fishing sector: the grey seal, the great cormorant, and regulation
of pikeperch harvesting. Within the framework of political ecology, develop-
ments in the current state of the fisheries are examined and the policy-making processes are analysed. Additionally, the notion of knowledge and the role
of both scientific knowledge and local ecological knowledge in the context of
fisheries management and fisheries management science are discussed.
Keywords: Fisheries, resilience, local ecological knowledge, seals, pikeperch
great cormorant, policy-making, The Common Fisheries Policy